IMPLEMENTASI MEDIA KARTU AKSARA BALI PADA KELOMPOK BELAJAR BAHASA BALI DI DESA PENGASTULAN, KECAMATAN SERIRIT, SINGARAJA - Darma Putra, Putu Adi (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2023)
This research aims to find out how the Balinese script card media is implemented in Balinese language learning groups in Pengastulan Village, what obstacles are encountered when implementing Balinese script card media in Balinese language learning groups, and what efforts are made to improve the ability to write Balinese script through card media Balinese script in Balinese language learning group students. This research was conducted on twenty-four Balinese Language Learning Group students at SD Negeri 1 Pengastulan and SD Negeri 3 Pengastulan, Grades 4 to 6. The research method used in this research is qualitative in the form of percentages displayed in table form, Balinese script cards to make it easier to learn Balinese. This research data was analyzed using theories relevant and related to this research, such as the implementation of Balinese script card media analyzed using Communication Theory. The second and third discussions are the obstacles encountered when implementing the Balinese script card media and the efforts made to improve the ability to write Balinese script analyzed using Value Theory. In collecting data, daily diary instruments, free interview guidelines and observation guidelines were used. The results of this research can be shown as follows. The implementation of the Balinese Literacy Card Media in the Balinese Language Learning Group was obtained from the results of coordination and interviews with several figures, parents of students and other supporting figures, who indeed supported the conduct of research in the field, which in turn made the research results more optimal and the data obtained was in accordance with those in the field. There are obstacles encountered when implementing the Balinese script card media, but with these obstacles, researchers must find efforts to improve the ability to write Balinese script, through the Balinese script card media for students in the Balinese Language Learning Group, which will later achieve proper Balinese language learning. effective.